2018
DOI: 10.18203/2349-2902.isj20184632
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic indicators affecting functional outcome in Zone II flexor tendon repairs

Abstract: Background: Advances in surgical technique and rehabilitation have transformed zone II flexor tendon injuries from an inoperable no man's land to a standard surgical procedure. Despite these advances, many patients develop a substantial range of motion limiting adhesions after primary flexor tendon repair. To analyze the prognostic indicators, which influence the functional outcome in Zone II Flexor tendon injuries in fingers.Methods: 21 patients with 28 Zone II Flexor Tendon Injuries who presented to us withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 21 publications
0
5
0
2
Order By: Relevance
“…In Tabriz, Iran, the range of motion was assessed by Strickland classification, and the results were as follows: 78.3% excellent, 10% good, 5% moderate and 6.7% bad, and there was no significant difference between the results in men and women and in immediate and delayed primary repair 24 . The range of motion was excellent and good in 71% of subjects, moderate in 34%, and bad in 15% of individuals 25 .…”
Section: Discussionmentioning
confidence: 99%
“…In Tabriz, Iran, the range of motion was assessed by Strickland classification, and the results were as follows: 78.3% excellent, 10% good, 5% moderate and 6.7% bad, and there was no significant difference between the results in men and women and in immediate and delayed primary repair 24 . The range of motion was excellent and good in 71% of subjects, moderate in 34%, and bad in 15% of individuals 25 .…”
Section: Discussionmentioning
confidence: 99%
“…When the hand surgeon fails to remake this anatomical relationship, it will restrain tendon to glide and increase the risk of adhesion and restrict the digital movement. 10,11…”
Section: Introductionmentioning
confidence: 99%
“…When the hand surgeon fails to remake this anatomical relationship, it will restrain tendon to glide and increase the risk of adhesion and restrict the digital movement. 10,11 In the middle of 1970s, Duran and Houser, 12 delineate their method which involved "controlled passive motion" and reported that the restrictive adhesions tendon may be prevented with 3 until 5 mm length of tendon excursions. Concomitantly, Kleinert et al 13 investigated the promising outcome using direct passive motion postsurgical with a rubber band as an orthosis to pull back the finger and permit active finger extension, with producing passive flexion movement of finger.…”
Section: Introductionmentioning
confidence: 99%
“…When the hand surgeon fails to remake this anatomical relationship, it will restrain tendon to glide, increase the risk to adhesion and restrict the digital movement. 10 11 …”
Section: Introductionmentioning
confidence: 99%
“…Quando o cirurgião de mão não consegue refazer esta relação anatômica, ele restringirá o deslizamento do tendão, aumentará o risco de adesão e restringirá o movimento digital. 10 11 …”
Section: Introductionunclassified